Developing the "120 by 20" Goal for the Global FP2020 Initiative. Issue 1 (10th March 2014) - Brown, Win; Druce, Nel; Bunting, Julia; Radloff, Scott; Koroma, Desmond; Gupta, Srishti; Siems, Brian; Kerrigan, Monica; Kress, Dan; Darmstadt, Gary L.
Abstract : This report describes the purpose for developing a quantitative goal for the London Summit on Family Planning held in July 2012, the methodology behind its formulation, and the lessons learned in the process. The London Summit has evolved into the global initiative known as FP2020, and the goal has become "120 by 20, " or reaching 120 million additional users of modern contraceptive methods by 2020 in the world's poorest countries. The success of FP2020 will first be evaluated on the basis of quantitative verification to determine that the "120 by 20" goal was reached. More important, however, is the extent to which the goal today serves as a global rallying cry to mobilize resources and leadership around current family planning programs, with a focus on voluntary family planning and quality of care, and with an emphasis on meeting girls' and women's unmet needs and their right to practice contraception. We hope this article provides greater transparency and understanding of the FP2020 goal, and that the global goal spurs annual monitoring of progress toward national goals in the world's poorest countries.